Pembinaan Prestasi Cabang Olahraga Catur PERCASI Kota Semarang Tahun 2020 (Universitas Negeri Semarang, 2021)
Purpose of this study to determine the implementatation of chess performance in Percasi Kota Semarang. This research use descriptive qualitative approach. Data collection using the method of observation, interview, and documentation. The subjects in this study were administrators, coaches and athletes. The validity check used used data triangulation technique. Data analysis activities include data collection, data reduction, data presentation, and drawing conclusions. The result showed that the implementation of performance coaching in Percasi Kota Semarang was good, Massive is carried out by monitoring tournament and in collaboration with tradisional leaders and the education office. Nurseries are carried out by three methods, namely bringing in a personal trainer, participating in a special coaching club or public club in the city of Semarang and self-learning using chess books or computers. The human resources of Percasi Kota Semarang fall into good criteria, some coaches have licenses, atheletes have high fighting spirit and internasional level achievements, and management has been running according to its duties. The training program at Percasi Kota Semarang falls into the suffcient criteria, where the training programs are not all structured. The facilities and infrastructur for Percasi Kota Semarang are good, but there is only a lack of a centralized training ground. As well as the funding for Percasi Kota Semarang, Percasi Kota Semarang received from KONI Kota Semarang.